Attaining sustainable high-rise office buildings in warm-summer-cold-winter climates: a case study on Frankfurt - Hong, Yuanda; Deng, Wu; Ezeh, Collins I; Peng, Zhen (Oxford University Press, 2019)
Attaining sustainability in high-rise office buildings necessitates determining the major elements and their associating impacts on the energy performance of this building typology. This study investigates the impact of architectural and engineering features on the energy performance of high-rise office buildings within a warm-summer-cold-winter climate. A rectangular building plan form with a 1:1.44 plan ratio, vertical split core position and central atrium presented the best building performance. The plan form, core position and atrium effect accounted for 59, 30 and 11%, respectively, of an estimated 20.6% building energy savings. Furthermore, exploiting passive strategies founded on the climate and building features as defined by `PassivHaus’ standards further reduced the building energy usage.